Dirac Operators with Generalized Coefficients and Their Line Integration - Ludkowski, S. V. (Communications in Mathematics and Applications, 2013)
Dirac operators with generalized coefficients are studied. Their non-commutative line integration over Cayley-Dickson algebras is investigated.
Keywords: Hypercomplex numbers; Cayley-Dickson algebras; Dirac operator; Non-commutative; Generalized coefficients; Line integration; Partial differential operator